Analisis Terhadap Kepatuhan Perbankan terhadap Regulasi Anti Pencucian Uang (APU) dalam Sistem Hukum Perbankan - Diva Pramesti Islami; Alexandra Exelsia Saragih; Azzahra Arifin; Nabila Adifia Azzahra; Satino S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research has the potential to be misused by people who use banking facilities that allow direct and online transactions while still paying attention to the security of international and domestic transactions because it is motivated by the rapid development of the digital world in the banking system. With this development, all banks are becoming more aggressive in providing special policies for all banking services and all services related to financial services throughout the country on a regular basis through regulators, in this case Bank Indonesia, and policies from the OJK. Based on this, Bank Indonesia issued a Bank Indonesia Regulation concerning the principle of prudence in banking services to all customers without exception, while still paying attention to customer comfort in transactions so that customers remain comfortable and safe in storing their money in the Bank. The criminal offenses considered in this research are legal studies or analyzes of the rules in regulations issued by the Regulator as a whole which deal with Special Crimes, namely the crime of money laundering. The concrete manifestation of the issuance of APU regulations by Bank Indonesia can reduce the incidence of money laundering involving banks because after the issuance of the APU regulations, every banking institution is obliged to implement them.